Potency, Safety, and Pharmacokinetic Profiles of Potential Inhibitors Targeting SARS-CoV-2 Main Protease - Mengist, Hylemariam Mihiretie; Mekonnen, Daniel; Mohammed, Ahmed; Shi, Ronghua; Jin, Tengchuan (Frontiers in Pharmacology, 2021)
Effective, safe, and pharmacokinetically suitable drugs are urgently needed to curb the ongoing COVID-19 pandemic. The main protease or 3C-like protease (Mpro or 3CLpro) of SARS-CoV-2 is considered an important target to formulate potent drugs corresponding to its crucial role in virus replication and maturation in addition to its relatively conserved active site. Promising baseline data on the potency and safety of drugs targeting SARS-CoV-2 Mpro are currently available. However, pre-clinical and clinical data on the pharmacokinetic profiles of these drugs is very limited. This review discusses the potency, safety and pharmacokinetic profiles of potential inhibitors of SARS-CoV-2 Mpro and forward directions on the development of future studies focusing on COVID-19 therapeutics.